A Frequency Reconfigurable Band-notched UWB Dielectric Resonator Antenna with a Wide-tuning Range for Cognitive Radio Systems. Issue 4 (4th July 2021) - Abioghli, Mehdi; Keshtkar, Asghar; Naser-Moghadasi, Mohammad; Ghalamkari, Behbod
Abstract : A new reconfigurable band-notched ultra-wideband (UWB) dielectric resonator antenna (DRA) has been designed and fabricated for cognitive radio (CR) applications. The UWB antenna design comprises a dielectric resonator as a radiation element, a ground plane, and a microstrip feed line. The frequency band's rejection mechanism is achieved by cutting two slots and adding an L-shaped stub on the ground plane. The reconﬁgurable function is created by PIN diode switches to change the current distribution path on the ground plane. A preliminary model of the DRA was fabricated, and its efficiency was verified. The proposed antenna occupies an area of 40  × 40  × 7.3 mm. The simulated and measured results have demonstrated suitable radiation patterns attained by the proposed antenna, which operates within the UWB frequency range of 3–11 GHz. Moreover, the antenna has shown an ability by rejecting switchable bands to achieve the WiMAX (3.2–3.65 GHz), WLAN 5 GHz (4.8–6 GHz), and ITU 8 GHz (8–8.3 GHz). Also, this antenna can be operated as dual and triple band-notched antennas.